Selective Substitution of POCl3 with Organometallic Reagents: Synthesis of Phosphinates and Phosphonates - Verbelen, Bram; Dehaen, Wim; Binnemans, Koen (Synthesis, 2018)
The selectivity of the substitution reaction of phosphoryl chloride with organometallic reagents was investigated using NMR spectroscopy. This led to the discovery that the selectivity of the substitution reaction can be tuned by choosing a proper organometallic reagent. A phosphinate could be obtained by using a Grignard reagent whereas an organozinc reagent provided a phosphonate. Based on these results, one-pot synthetic methods for the preparation of phosphinates and phosphonates using commercially available starting materials were developed. Both methods allow the synthesis of a broad range of either phosphinate or phosphonate derivatives in a straightforward and general procedure. Moreover, using these one-pot procedures, mixed systems substituted with different alkyl/aryl groups can be prepared.
Keywords: selectivity; substitution; phosphoryl chloride; phosphinate; phosphonate; Grignard reagent; organozinc reagent